Retrieving Information for Urgency Medical Services using Abundant Data Processing Method - Balaji, V; Dinagaran, D; Rajmohan, R (IJRDO -Journal of Computer Science Engineering, 2015)
The Internet of Things (IoT) is the interconnection of uniquely identifiable embedded computing devices within the existing internet infrastructure. Delivering clinical information of patient at the point-of-care to physicians is critical to increase the quality of healthcare services, especially in emergency time. However, clinical data are distributed in different hospitals. It is sometimes difficult to collect clinical data of patient ubiquitously in case of urgency. In order to support the ubiquitous content accessing a resource model is first proposed to locate and get clinical data which are stored in heterogeneous hospital information systems using Hadoop Distributed File System. In the proposed method clinical data of patient is defined as resource with unique URL address. Related clinical data of one patient is collected together to form a combinational resource, and could be accessed by physician if authority is assigned to the physician, by using a mongo dB database technique efficiently in big data applications for better performance and scalability. This type of database support faster execution of queries compared to non-relational databases. By implementing the system that combines IoT with Big Data is built to provide quick and effective for different patients.